2020
DOI: 10.3390/cancers12071798
|View full text |Cite
|
Sign up to set email alerts
|

The Lipase/Amylase Ratio (LAR) in Peripheral Blood Might Represent a Novel Prognostic Marker in Patients with Surgically Resectable Pancreatic Cancer

Abstract: Pancreatic enzymes might play a pivotal role in the pathophysiology and prognosis of pancreatic cancer. The aim of this study is to investigate the lipase/amylase ratio (LAR), representing a marker previously used in the differentiation of pancreatitis, as a potential prognostic marker in pancreatic cancer. Data from 157 surgically treated patients with ductal pancreatic adenocarcinoma and 351 patients with metastatic disease were evaluated retrospectively. Cancer-specific survival (CSS) was considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In acinar cells, we detected high expression of regenerating family member genes, such as REG1B and REG3A in the naïve group only. Higher expression of amylases and lipase genes were found in both treated groups, which have been previously associated with chronic pancreatitis and pancreatic cancer ( Figure S7A ) (Raphael et al, 2016; Stotz et al, 2020; Lasher et al, 2019). In endothelial cells, we observed an upregulation in metallothioneins in treated samples, particularly in gemcitabine+nab-paclitaxel samples.…”
Section: Resultssupporting
confidence: 60%
“…In acinar cells, we detected high expression of regenerating family member genes, such as REG1B and REG3A in the naïve group only. Higher expression of amylases and lipase genes were found in both treated groups, which have been previously associated with chronic pancreatitis and pancreatic cancer ( Figure S7A ) (Raphael et al, 2016; Stotz et al, 2020; Lasher et al, 2019). In endothelial cells, we observed an upregulation in metallothioneins in treated samples, particularly in gemcitabine+nab-paclitaxel samples.…”
Section: Resultssupporting
confidence: 60%
“…3.2.1.1) catalyze the hydrolysis of α -1,4 glycosidic bonds present in starch, glycogen and other related carbohydrates to low molecular weight products, such as glucose, maltose and maltotriose [ 4 , 5 , 6 , 7 , 8 ]. These enzymes are present in plants, animals and microorganisms [ 9 ] and have extensive applications in medicine [ 10 , 11 , 12 , 13 , 14 ], textiles [ 11 ], detergent [ 11 ], fermentation [ 11 ] and the food industry [ 4 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to industrial use, α -amylase from porcine pancreas is used for example in health food research [ 16 , 17 , 18 ], to assay resistant starch (RS), not broken down by human enzymes in the small intestine [ 19 ] and is also used in medical diagnostics [ 12 , 13 , 14 ]. One of the problems is effective diagnostic methods allowing for the prognosis of pancreatic cancer of cancer, which is an exceptionally aggressive tumour with high mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-world studies reported in the literature have included estimates of the prognostic impact of patient and disease characteristics in patients receiving systemic therapy for mPDAC. [17][18][19][20][21] Such studies have been limited in sample size due to a reliance on one or a limited number of study centers or a focus on patients receiving a particular drug regimen. This has limited their usefulness for guiding decision-making in the treatment of patients with mPDAC.…”
Section: Introductionmentioning
confidence: 99%